Cyclic compression emerged dual effects on the osteogenic and osteoclastic status of LPS-induced inflammatory human periodontal ligament cells according to loading force - Ru Jia; Yingjie Yi; Jie Liu; Dandan Pei; Bo Hu; Huanmeng Hao; Linyue Wu; Zhenzhen Wang; Xiao Luo; Yi Lu (BMC, 2020)
Abstract Background Appropriate mechanical stimulation is essential for bone homeostasis in healthy periodontal tissues. While the osteogenesis and osteoclast differentiation of inflammatory periodontal ligament cells under different dynamic loading has not been yet clear. The aim of this study is to clarify the inflammatory, osteogenic and pro-osteoclastic effects of different cyclic stress loading on the inflammatory human periodontal ligament cells (hPDLCs). Methods hPDLCs were isolated from healthy premolars and cultured in alpha minimum Eagle's medium (α-MEM). Lipopolysaccharides (LPS) were used to induce the inflammation state of hPDLCs in vitro. Determination of LPS concentration for the model of inflammatory periodontium was based on MTT and genes expression analysis. Then the cyclic stress of 0, 0-50, 0-90 and 0-150 kPa was applied to the inflammatory hPDLCs for 5 days respectively. mRNA and protein levels of osteogenic, osteoclastic and inflammation-related markers were examined after the treatment. Results MTT and RT-PCR results showed that 10 μg/ml LPS up-regulated TNF-α, IL-1β, IL-6, IL-8 and MCP-1 mRNA levels (P < 0.05) and did not affect the cell viability (P > 0.05). The excessive loading of stress (150 kPa) with or without LPS strongly increased the expression of inflammatory-related markers TNF-α, IL-1β, IL-6, IL-8, MCP-1 (P < 0.05) and osteoclastic markers RANKL, M-CSF, PTHLH and CTSK compared with other groups (P < 0.05), but had no significant effect on osteogenic genes. While 0-90 kPa cyclic pressure could up-regulate the expression of osteogenic genes ALP, COL-1, RUNX2, OCN, OPN and OSX in the healthy hPDLSCs. Conclusions Collectively, it could be concluded that 0-150 kPa was an excessive stress loading which accelerated both inflammatory and osteoclastic effects, while 0-90 kPa may be a positive factor for the osteogenic differentiation of hPDLCs in vitro.